A novel therapy for influenza-induced pneumonia - Jerry M Cuttler; Edward J Calabrese (Journal of Radiation and Cancer Research, 2021)
This article recommends incorporating low-dose, lung radiation therapy into the treatment strategy for patients hospitalized with pneumonia due to influenza. This proposal is based on the history of 863 patients with severe bacterial or viral pneumonia. The lives of 717 of these patients were saved by the application of one X-ray treatment to their lungs. Since many tens of thousands of people die every year from influenza, complementary treatments that are safe and effective are needed. Low-dose radiation should become a life-saving component to the overall clinical patient management for this condition.